PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE TERHADAP MINAT DAN HASIL BELAJAR BIOLOGI PADA SISWA K E LAS XI IPA SMA NEGERI I MANOKWARI - Parinding, Margaretha; Antoh, Alfred A. (Jurnal Ilmu Pendidikan Indonesia, 2015)
The goals of this study are to know the influence of Cooperative Learn in g Model Type Scramble application on student sâ interest in learning Biology and to know the impact of this model application on the learning outcomes of students on the subject of Cell Structure and Function. The study design is a Pre-Experiment al De sign in a "One-Gro up P rete st-Posttest Design". This st udy is t he Ex-Po st Facto where the independent variable is the Cooperative Learning Model Type Scrambleand the dependent variable is the interest and learning outcomes. Questionnaire and test as instruments are used to measure studentsâ interest and learning outcomes. There were 32 research samples from students of C lass XI IPA I taken by using cluster random sampling. Analysis of data using qualitative data (by questionnaires) and quantitative (n-gain ) followed normality test and a simple linear regression. Result sfrom linear regression test of the scramble type model on student sâ interest show the calculatedt for coefficient a (2,366) and b (6,317) are both larger thant from the table which is 1,697 means that both coefficient a and b are significant. The significance of a interest. And b coefficient shows an influence of the model on stude nt sâ Mean while for the test of the scramble type model on learning outcomes show the Calculatedt for coefficient a (3,09 3) and b (6,11 8) are also larger thant from the table means that both a and b are significant. Key Words: Cooperative learning model, scramb le, interest, Learning Outcomes Biology.